ACCUMULATION BEHAVIOUR OF ALLANTOIN IN THE UNDERGROUND PHYTOMASS OF THE BORAGINACEAE FAMILY AND ITS ROLE IN ADAPTING THE PLANTS TO ADVERSE ENVIRONMENTAL FACTORS - A. Ya. Tamakhina; A. A. Akhkubekova; A. B. Ittiev (Юг России: экология, развитие)
Aim. The aim of the work described herein was to study the dynamics of allantoin accumulation in the underground phytomass of Echium vulgare L., Symphytum caucasicum M. Bieb. and S. asperum Lepech. as well as to clarify the role of allantoin in plant adaptation to stress factors.Methods. We studied the roots of plants growing in the foothill (Nalchik, 490–512 m above sea level) and the mountain zones of the Kabardino-Balkarian Republic (Terskol village, 2530 m above sea level; Verkhnyaya Balkaria village, 2680 m above sea level). The roots were collected at the stages of rosetting, flowering, fruiting and at the end of the growing season. Aqueous-alcoholic extracts of shredded roots were analyzed by high-performance liquid chromatography.Results. The highest content of allantoin in the roots of Echium vulgare, Symphytum caucasicum, S. asperum plants was noted at the end of the growing season, respectively 0.915; 0.342–0.658; 2,842–3,426%. Under conditions of low temperatures and increased solar radiation, the content of allantoin in the roots increases 1.2–1.9 times as compared with the plants of the foothill zone.Conclusion. Allantoin plays an important role in the process of adapting species of the family Boraginaceae to oxidative stress caused by hypothermia and increased solar radiation.